Pengaruh Pendapatan, Jarak Tempuh, Dan Lama Waktu Berkunjung Terhadap Kesediaan Wisatawan Membayar Retribusi Tiket Pada Objek Wisata Pulau Mandeh - Nilmadesri Rosya; Yolamalinda Yolamalinda (Universitas Negeri Padang, 2019)
his study aims to determine the willingness of visitors to pay entrance ticket retribution on the tourist attraction of Mandeh Island in the South Coast. The hypothesis was tested using multiple linear regression analysis. The data used are primary data in the form of interviews using questionnaires to 50 visitors in Mandeh Island Tourism Area. Sampling uses accidental sampling. Data analysis used Multiple Linear Regression test and hypothesis test with t test and F test. The results showed that: (1) there is a positive influence between income partially on willingness to pay retribution with a coefficient value of 0.035, the value of tcount is 0.598 <t table of 1.985; (2) there is a positive influence between partial mileage on willingness to pay retibusi with a coefficient value of 0.432 tcount of 3.97> ttable 1.985 (3) there is no negative influence between the length of time visiting the willingness to pay retribution with a coefficient of 0.052 and tcount amounting to 0.456> ttable 1.985; (4) there is a positive and significant influence between income, distance traveled and the length of time of visit available to the willingness to pay levies on the mandatory tourist area with F count 6.588> Ftable 2.70.